An exploratory assessment of weight loss videos on YouTube™. (October 2017) - Basch, C.H.; Fung, I.C.-H.; Menafro, A.; Mo, C.; Yin, J.
Abstract: Objective: To describe the variation in contents between different video sources on YouTube™ regarding weight loss. Study Design: The 100 most widely viewed weight loss videos on YouTube™ were selected for manual coding. Methods: Videos were manually coded based on sources and contents, we also identify themes for each of the videos. Univariate logistic regression was used to assess difference in contents between videos from different sources. Results: After excluding two videos, a sample of 98 videos remained. Among them, there were 74 consumer-generated videos, 12 news videos, and 12 from commercial television and companies. Collectively, the 98 videos were viewed more than 365 million times. The odds of mentioning ongoing lifestyle that includes long-term changes in daily eating was 90% less in commercial and company videos compared to consumer videos (odds ratio [OR] = 0.10, 95% confidence interval [CI] 0.01–0.85, P = 0.03). The odds of showing a female talking in the video about weight loss was 81% less in news videos compared to consumer videos (OR = 0.19, 95% CI 0.05–0.68, P = 0.01). In addition, commercial and company videos were found to be 18 times as likely to carry a theme on workout as consumer videos (OR = 18.13, 95% CI 3.60–91.22, P < 0.01). Conclusion: Public health professionals need to be more creative to make their videos popular if they want to reach a wide audience. Highlights: Three in four most viewed weight loss-related videos are consumer-generated. Commercial videos focus on workout but not long-term balanced diets. Consumer videos often feature females talking about weight loss. Among the top 100 viewed weight loss videos, only one was professional.